Pengaruh Kompetensi Kepribadian Guru Terhadap Kinerja Guru Di SD Se-Kecamatan Danau Sipin Kota Jambi - Yulianti, Febi; Kasiono, Kasiono (Universitas Batanghari Jambi, 2026)
This study aims to determine the description and influence of teacher personality competency on teacher performance in elementary schools in Danau Sipin District, Jambi City. This study uses quantitative research with a research design using Simple Regression Analysis. The research subjects were 37 teachers in three elementary schools, namely SDN 26 Jambi City, SDN 68 Jambi City, and SDN 143 Jambi City. The data collection technique used a questionnaire. Data analysis techniques were Normality Test, Homogeneity Test, and Simple Regression Analysis. The results of this study indicate that the coefficient value of B constant = 34.402 states that if the personality competency variable is ignored, then teacher performance = 0.208. Based on this, a simple regression equation can be made, namely Y = a + Bx is Y = 34.402 + 0.208X with a calculated t value of X = 4.133. Thus, the hypothesis that states there is a significant influence between teacher personality competency on the performance of elementary school teachers in Danau Sipin District, Jambi City.